COVID-19 Vaccine Coverage and Factors Associated with Vaccine Hesitancy: A Cross-Sectional Survey in the City of Kinshasa, Democratic Republic of Congo - Pierre Z. Akilimali; Landry Egbende; Dynah M. Kayembe; Francis Kabasubabo; Benito Kazenza; Steve Botomba; Nguyen Toan Tran; Désiré K. Mashinda (Vaccines, 2024)
Vaccination against COVID-19 has been the main strategy used by most countries to limit the spread of the virus. However, vaccine uptake has been low in Africa, leading to the implementation of several interventions in order to improve vaccine coverage. This study was conducted due to the lack of information about COVID-19 vaccine coverage and the factors associated with vaccine hesitancy. This cross-sectional study was carried out in Kinshasa city using multi-stage random sampling. A total of 2160 households were included in this study. The data were analyzed using Stata 17 software. The means and standard deviations were computed for continuous data that followed a normal distribution, whereas proportions together with their 95% confidence intervals (CIs) were computed for categorical variables. The connections between dependent variables and each independent variable were tested using either Pearson's chi-square test or Fisher's exact test. The logistic regression method was employed to determine the factors that are linked to hesitation in obtaining the COVID-19 immunization. The majority of respondents were aged between 25 and 34 and 35 and 49 (28.9%). During this study, 15% (95% CI [13.25–17.9]) of respondents had received at least one dose of the COVID-19 vaccine. The prevalence of vaccine hesitancy was 67% (CI95%:64.9–69.1). Among the reasons given for refusing to be vaccinated, most respondents cited concerns about the vaccine being unsafe or causing adverse reactions (45%). Among the reasons given for accepting the vaccine, 26% thought that the vaccine prevented superinfection. The factors associated with hesitancy toward the COVID-19 vaccine were female gender, an age of less than 35 years, and living in non-slum households. Despite the interventions implemented across the country, the reluctance to be vaccinated remains a problem; this could lead to poor health outcomes, especially among the elderly and those with pre-existing conditions. It is important to step up awareness-raising campaigns in the community in order to increase the uptake of vaccination.